Review of the protective effects of Compound 21 and valsartan in iso-induced heart failure in rats - Zeynep, Ulutas; Tarik, Kivrak; Onural, Ozhan; Nigar, Vardi; Hakan, Parlakpinar; Burhan, Ates; Necip, Ermis (Wiley, 2019)
[Abstract Not Available]